PRODUCTION OF GLASS - FUKUOKA TAKANAO (1998)
PROBLEM TO BE SOLVED: To obtain glass free from striated defect by a sol-gel method by uniformly holding colloid particle density in a sol, in the production of glass by the sol-gal method. SOLUTION: In the production method of glass by the sol-gel method, while the colloid particle density in the sol is uniformly maintained in a gelatin process of the sol, the sol is gelated. When the sol is poured into a gelating container at a surrounding temp., the temp. of the sol poured into the gelating container is different from the temp. of the gelating container. In order to equalize those temps. the temp. of the sol or the container is adjusted to be equal, Then the container in which the sol is poured in placed at the equal temp. thus to allow the sol to gelate. The temps, of the sol and the gelating container are preferably equal but is the temp. difference between the sol and the gelating container is in the range of not cauing fluidity due to the temp. difference that is, temp. difference between the sol and the gelating container of within 7 deg.C, it is acceptable and any problem does not occur.